Coping With Stress: The Mitokine GDF-15 as a Biomarker of COVID-19 Severity - Ahmed, Darakhshan Sohail; Isnard, Stéphane; Berini, Carolina; Lin, John; Routy, Jean-Pierre; Royston, Léna (Frontiers in Immunology, 2022)
Growth differentiation factor 15 (GDF-15) is a transforming growth factor (TGF)-β superfamily cytokine that plays a central regulator role in metabolism regulation. Produced in response to mitochondrial stress, oxidative stress, tissue damage or hypoxia, this cytokine/mitokine has emerged as one of the strongest predictors of disease severity for inflammatory conditions, cancers, and infections. Reports suggest that GDF-15 plays a tissue protector role via sympathetic and metabolic adaptation in the context of mitochondrial damage, however the exact mechanisms involved remain uncertain. In this review, we discuss the emergence of GDF-15 as a distinctive marker of viral infection severity, especially in the context of COVID-19. We will critically review the role of GDF-15 as an inflammation-induced mediator of disease tolerance, through metabolic and immune reprogramming. Finally, we will discuss possible mechanisms of GDF-15 elevation during the COVID-19 cytokine storm. Altogether, this mitokine seems to be involved in disease tolerance to viral infections including SARS-CoV-2, paving the way for novel therapeutic interventions.